2019
DOI: 10.1136/svn-2018-000163
|View full text |Cite|
|
Sign up to set email alerts
|

Intravenous tirofiban therapy for patients with capsular warning syndrome

Abstract: BackgroundCapsular warning syndrome (CWS) is defined as recurrent episodes of transient ischaemic attacks ≥3 times during a short time frame. There is no effective therapy to stop these attacks. We, herein, report our experience of using intravenous tirofiban to treat CWS.MethodsAll patients with CWS in our hospital from January 2013 to September 2017 were reviewed. Patients in tirofiban group (T-group) were treated by intravenous tirofiban at 0.4 μg/kg/min for 30 min followed by 0.1–0.15 µg/kg/min infusion. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…These stereotypical attacks might be caused by the "thrombotic" process and overactivation of platelets [27][28]. The observational study of Meng [29] showed that intravenous tiro ban appeared to be effective and safe in stopping recurrent and uctuating symptoms in patients with capsular warning syndrome(CWS) and in improving the three-month prognosis. It has been suggested that tiro ban, via a more fast-acting and powerful action on the cerebral cortex, may help prevent CWS from progressing to infarction.…”
Section: Discussionmentioning
confidence: 99%
“…These stereotypical attacks might be caused by the "thrombotic" process and overactivation of platelets [27][28]. The observational study of Meng [29] showed that intravenous tiro ban appeared to be effective and safe in stopping recurrent and uctuating symptoms in patients with capsular warning syndrome(CWS) and in improving the three-month prognosis. It has been suggested that tiro ban, via a more fast-acting and powerful action on the cerebral cortex, may help prevent CWS from progressing to infarction.…”
Section: Discussionmentioning
confidence: 99%
“…SAO is a common cause of capsular warning syndrome (CWS), since CWS is most often due to small penetrating vessel hemodynamic disorder ( 25 , 26 ). A previous study on tirofiban showed that it could stop early symptomatic fluctuations and decrease the duration of functional impairments in patients with CWS compared with oral antiplatelet drugs ( 27 ). In addition, there is evidence that tirofiban is safe and efficacious in patients with ischemic stroke outside the thrombolytic therapy window compared with oral antiplatelet medications ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…Favorable outcomes using dual antiplatelet drugs (aspirin and clopidogrel) were reported in CWS 7,14) ; however, a confirmed therapeutic strategy in patients with CWS is uncertain 3) . In the preventive treatment of our patient, one or two antiplatelets agents were administered until the sixth hospitalization.…”
Section: Discussionmentioning
confidence: 99%